2021
DOI: 10.2478/aucft-2021-0002
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Analysis of Different Varietal of Fresh and Dried Figs by In Vitro Bioaccessibility of Phenolic Compounds and Antioxidant Activities

Abstract: Varietal and sun-drying effects on phenolic compounds and their antioxidant activity were investigated during the in vitro gastrointestinal digestion of fresh and dried figs. The total phenolic compounds (phenolic, flavonoids, and proanthocyanidin) and their antioxidant activity (ferric reducing power; free radical scavenging activity DPPH, and phosphomolybdenum test) were evaluated before and after digestion. The total phenolic compounds and the antioxidant capacities of fresh and dried figs obtained before d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 37 publications
0
0
0
Order By: Relevance
“…For example, a study conducted by Kehal and colleagues, using three fig cultivars in fresh and dried forms, showed that phenolic compounds and antioxidant capacity decreased during different digestion phases (oral phase > gastric phase > intestinal phase). The study also found that sun-drying and cultivar had no impact on the in vitro digestion of phenolic compounds and antioxidant activity from figs [88]. Alternatively, Kamiloglu and colleagues (2013) reported that the sun-drying of figs results in an increased bio-accessibility of total proanthocyanidin and chlorogenic acid content, as well as total antioxidant activity, compared to fresh figs; however, the bio-accessibility of anthocyanins (cyanidin-3-O glucoside and cyanidin-3-O rutinoside) was very low for fresh figs and anthocyanins were not detected in the dialyzed fraction of sun-dried figs [89].…”
Section: Bio-accessibility and Bioavailability Of Phytochemicals From...mentioning
confidence: 82%
See 1 more Smart Citation
“…For example, a study conducted by Kehal and colleagues, using three fig cultivars in fresh and dried forms, showed that phenolic compounds and antioxidant capacity decreased during different digestion phases (oral phase > gastric phase > intestinal phase). The study also found that sun-drying and cultivar had no impact on the in vitro digestion of phenolic compounds and antioxidant activity from figs [88]. Alternatively, Kamiloglu and colleagues (2013) reported that the sun-drying of figs results in an increased bio-accessibility of total proanthocyanidin and chlorogenic acid content, as well as total antioxidant activity, compared to fresh figs; however, the bio-accessibility of anthocyanins (cyanidin-3-O glucoside and cyanidin-3-O rutinoside) was very low for fresh figs and anthocyanins were not detected in the dialyzed fraction of sun-dried figs [89].…”
Section: Bio-accessibility and Bioavailability Of Phytochemicals From...mentioning
confidence: 82%
“…These absorbed nutrients or phytochemicals can then exert a biological action or be stored for future use [87]. The phenolic compounds from figs are not readily bio-accessible, as reported by various studies using in vitro gastrointestinal digestion models [52,88,89]. For example, a study conducted by Kehal and colleagues, using three fig cultivars in fresh and dried forms, showed that phenolic compounds and antioxidant capacity decreased during different digestion phases (oral phase > gastric phase > intestinal phase).…”
Section: Bio-accessibility and Bioavailability Of Phytochemicals From...mentioning
confidence: 99%
“…EOs contain monoterpenes, aldehydes, ketones, alcohols, ethers, and phenolic compounds that play a crucial role in preventing oxidation. Indeed, these compounds can be hydrogen atom donors to release radicals and convert them into more stable molecules (Kehal et al 2021).…”
Section: Oxidative Stabilitymentioning
confidence: 99%